Synthesis of Novel Ethyl Vanillate Derivative - Vijay D. Gangan,; Deepak A. Tupare,; Pradip S. Shelar,; Priyanka Bhandari,; Snehal D. Patel,; Karuna Bhagwat, (International Journal of Scientific Research in Science and Technology, 2025)
Vanillic acid (4-hydroxy-3-methoxybenzoic acid) is a dihydroxy benzoic acid derivative used as a flavoring agent. It is used in the synthesis of various active pharmaceutical ingredients such as Etamivan, Modecainide, Brovanexine, Vanitiolide, Vanyldisulfamide etc. In this paper, novel ester / hybrid derivative of vanillic acid was synthesized. This combinatorial synthesis of novel vanallic ester / hybrid derivative can be a useful approach to generate potent chemotherapeutic agents in developing new drug candidates.
Keywords: Vanillic acid; IR; 1HNMR; TOF MS; DCC; DMAP; etc